Vitamin D deficiency in obese adolescent women - Pajuelo R., Jaime (2016)
Introduction. Vitamin deficiency is being considered a public health problem. Objectives. To describe vitamin D status in female adolescents with obesity. Design. Observational, descriptive, analytical study. Location. Metropolitan Lima. Participants. Teenagers. Interventions. According to body mass index, 111 adolescents were studied, 58 were obese and 53 non-obese. A food survey was performed including those containing vitamin D and vitamin supplements. Waist circumference and blood pressure were obtained. Glucose, lipid profile and 25 hydroxyvitamin D were determined in serum. Vitamin D status was determined by Holick criteria. Statistical analysis used student-t test, chi-square and ANOVA, with a 95% confidence interval and a significance level of <0.05. Main outcome measures. Averages, confidence interval and prevalence. Results. Vitamin D deficiency (<20 ng/mL) was found in 10.8% of adolescents, 11.3% in non-obese and 10.3% in the obese. Average vitamin D intake was 1.8 ug (95% IC 1.4-2.2) in non-obese and 1.7 ug (95% IC 1.4-2.1) in the obese. Intake was 2.3 ug (95% IC 1.9-2.9) in those deficient and 1.7 ug (95% CI 1.4-2) in the non deficient. There was no association between vitamin D and cardiovascular risk factors. Conclusions. One out of each 10 adolescent women was vitamin D deficient and 2 of 10 had insufficient vitamin D.